Diversity and potency of indigenous yeast from some palm juices for bioethanol production - Trianik Widyaningrum; SUHARJONO SUHARJONO; TRI ARDYATI; AULANNI’AM AULANNI’AM (Society for Indonesian Biodiversity, 2020)
Abstract. Widyaningrum T, Suharjono S, Ardyati T, Aulanni’am A. 2020. Diversity and potency of indigenous yeast from some palm juices for bioethanol production. Biodiversitas 21: 318-325. Main energy source commonly used by the community comes from fossil energy, especially petroleum. The crisis of energy showed that Indonesia's fossil energy reserves are limited. Based on this fact it is important to develop alternative energy that environmentally friendly and sustain, especially bioethanol. The objective of this research was to diversity and potency of indigenous yeast from palm juice of Arenga pinnata Merr., Cocos nucifera L., Nypa fruticans Wurmb., and Borassus flabellifer L. for bioethanol production. Yeast from juice of the four species of palm was isolated using Yeast Malt Extract Agar (YMEA). Those isolates were screen base on ethanol production in coconut water media. The potential of yeast isolates was identified base on 18S DNA sequence similarity. The four potential isolates of yeast were A3A from A. pinnata, K1A from C. nucifera, N3E from N. fruticans, and S1A from B. flabellifer have highest production of ethanol are 8.6 %, 14.2 %, 9.0 %, and 9.2 % respectively. Four potential isolates of yeast were A3A and N3E, K1A, and S1A have relationship with Saccharomyces cerevisiae NRRL Y-12632T, Pichia manshurica IFO 10726T, and Candida tropicalis ATCC 20615 respectively.